Knowledge management and intellectual capital in networks of small- and medium-sized enterprises - Jordão, Ricardo (2018)
Purpose – The purpose of this paper is to propose a theoretical-conceptual model supporting the analysis of the effects of small- and medium-sized enterprises (SMEs) networks on knowledge management (KM) and intellectual capital (IC). Design/methodology/approach – The paper reviews literature on KM, IC and networks theories. The role of SMEs networks on KM and IC was discussed, analysing previous studies that supported the proposition of the model in question. In such model SMEs networks are seen as knowledge networks which are analysed in terms of the network formation process, the context, the strategy, the organisational culture and the stimuli for the sharing of knowledge. KM is observed in terms of knowledge creation, systematisation and sharing. Finally, IC encompasses human capital, structural capital and relational capital. It is noteworthy that KM and IC were considered deeply and closely related. Findings – The conclusions obtained help to fill an important gap in the management, accounting, KM and IC literature, showing that the processes of creating, acquiring, maintaining, systematising and sharing information and knowledge and IC generation in SMEs networks can be influenced by the network formation process, by the organisational context, as well as by the strategy, organisational culture and stimuli to sharing knowledge. Research limitations/implications – The paper provides a theoretical contribution by increasing understanding of the effect of SMEs networks on KM and IC practices – an understanding still at the early stages in the literature. Moreover, the originality of the model proposed extends the relevance of this research, as the literature does not contain a sufficiently established and tested approach that simultaneously provides a clear view of the relations between SMEs, networks, KM and IC, highlighting how SMEs can use networks as a strategy to achieve a more effective management of the knowledge assets forming IC. So, the paper offers several avenues for future research. Practical implications – Based on previous empirical research, it was perceived that the original model presented in this paper is consistent, collaborating to improve management practice, providing a competitive benchmarking process. This can allow analysts, managers and other decision makers, by using SMEs networks to improve organisational performance, innovation, sustainability, competitiveness and value. Originality/value – The paper presents an innovative theoretical-conceptual model focussed on the role of SMEs networks on KM and IC, indicating a strong link between the former and the latter in such enterprises in terms of performance, innovation, sustainability, competitiveness and value, an issue whose understanding, although quite relevant, is still incipient in the literature.